Biochemical characterization of the flagellar stator-associated inner membrane protein FliL from Vibrio alginolyticus. (7th January 2017) - Kumar, Ananthanarayanan; Isumi, Miyu; Sakuma, Mayuko; Zhu, Shiwei; Nishino, Yuuki; Onoue, Yasuhiro; Kojima, Seiji; Miyanoiri, Yohei; Imada, Katsumi; Homma, Michio
Abstract : The flagellar motor is embedded in the cell envelope and rotates upon interaction between the stator and the rotor. The rotation is powered by ion flow through the stator. A single transmembrane protein named FliL is associated with torque generation in the flagellar motor. We established an Escherichia coli over-expression system for FliL of Vibrio alginolyticus, a marine bacterium that has a sodium-driven polar flagellum. We successfully expressed, purified, and crystallized the ca. 17 kDa full-length FliL protein and generated a construct that expresses only the ca. 14 kDa periplasmic region of FliL (ΔTM FliL). Biochemical characterization and NMR analysis revealed that ΔTM FliL weakly interacted with itself to form an oligomer. We speculate that the observed dynamic interaction may be involved in the role of FliL in flagellar motor function.